Using a Fixed-Bed of Wheat Straw-Derived Biochar to Enhance Cracking of a Mixture of Four Pyrolysis Vapor Model Compounds - Di Stasi, Christian; Alvira, Darío; Manyà, Joan J.; González, Belén (Jornada de Jóvenes Investigadores del I3A, 2018)
The aim of this work is to test the capacity of a biochar-based porous material to enhance the cracking of pyrolysis vapors. Biochar is a sustainable material obtained from renewable resources and a relatively low cost alternative to the metal-containing catalysts used in catalytic cracking.